2009
DOI: 10.1149/1.3205555
|View full text |Cite
|
Sign up to set email alerts
|

Locally-Resolved Study of Degradation in a SOFC Repeat-Element

Abstract: The locally-resolved degradation behavior was studied during 1900 hours in an SOFC repeat-element. In-situ measurements of local electrochemical performance were made on 18 locations over a segmented anode-supported cell. The evolution of local current densities, overpotentials and area-specific resistances was studied, showing a reorganization of the electrochemical reaction with time. The extent and the spatial distribution of degradation were established for different electrochemical reactions steps using i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…An anode-supported cell, with an active LSM-YSZ composite cathode and a LSC current collection layer, was tested over 1900 h around 1073 K. The evolution of electrochemical performance was measured in-situ on 18 locations distributed within a cell (1). Electrochemical impedance spectroscopy (EIS) measurements revealed that principally the cathode was affected by degradation, as indicated by large differences at the characteristic frequency attributed to dissociative adsorption of O 2 (cf Figure 1).…”
Section: Locally-resolved Degradation Studymentioning
confidence: 99%
“…An anode-supported cell, with an active LSM-YSZ composite cathode and a LSC current collection layer, was tested over 1900 h around 1073 K. The evolution of electrochemical performance was measured in-situ on 18 locations distributed within a cell (1). Electrochemical impedance spectroscopy (EIS) measurements revealed that principally the cathode was affected by degradation, as indicated by large differences at the characteristic frequency attributed to dissociative adsorption of O 2 (cf Figure 1).…”
Section: Locally-resolved Degradation Studymentioning
confidence: 99%
“…Only a minor Cr amount is found in these samples and the Cr-poisoned cathode area is confined to the electrolyte/cathode interface. The small amount of Cr in samples 2-6 compared to sample 1 is due to the trapping of volatile Cr species by the reactive LSC at the air inlet regions of the cell; the preferential distribution of Cr on the LSC CCL surface was already reported in previous publications (17,19). However, the results from Fig.…”
Section: Cr Profilingmentioning
confidence: 54%
“…), with additional periodic electrochemical testing: current‐voltage ( i‐V ) characteristics, which give the integral picture of the system's capability to produce electrical energy, combined with EIS in selected working points, which can evaluate components in the overall degradation. A specialized approach is the use of segmented single repeating unit (SRU) testing including local EIS (on each electrode segment), which allows to pinpoint the local character of degradation phenomena and to couple this with targeted post‐test analysis 35,36 . The final stage of such a complex study is post‐mortem analysis, which visualizes some of the morphological and compositional changes due to degradation effects 17,37 …”
Section: Introductionmentioning
confidence: 99%
“…42 – cannot avoid long‐term tests (several years) to mimic real operation. The results of the NEDO project described above 11–38 arise from evaluation under conditions in which heat or flow distribution is well controlled, in optimized stack design and under rated operation conditions. However, these large‐scale campaigns are less appropriate for iterative optimization of new materials, architecture or operating modes, nor convenient for day‐to‐day implementation in a SOC development company.…”
Section: Introductionmentioning
confidence: 99%